Assessing and Optimizing the Range of UHF RFID to Enable Real-World Pervasive Computing Applications - Hodges, Steve; Thorne, Alan; Mallinson, Hugo; Floerkemeier, Christian (Proceedings of Pervasive 2007, 2007)
Radio frequency identification (RFID) may be used to automatically detect, locate and/or identify objects, making it an ideal candidate for many pervasive computing applications. As RFID technology improves in terms of cost and performance, it is increasingly being explored in a variety of applications, ranging from eldercare through to the smart supply chain. However, while passive UHF RFID has many benefits over other RFID variants, reliable operation as the tag moves in the environment is inherently difficult to predict and can represent a significant challenge. In this paper, we present a novel and practical experimental method called attenuation-thresholding which may be used to characterize the operating range of such RFID systems. The results presented demonstrate the advantages of our method over the conventional read-rate approach. We also demonstrate a novel approach to collecting the measurements in range characterization experiments using robotic automation. Finally, we show how the application of attenuation-thresholding in combination with robotic automation can be used to optimize tag placement on an object. In addition to the clear relevance of this work to the many RFID-based pervasive computing applications reported in the literature and currently under development, it also has broad applicability in other RFID application domains. We conclude with a number of ideas for future extensions to this work.